180k views
1 vote
Please help and explain

Please help and explain-example-1
User Zorgbargle
by
5.1k points

1 Answer

2 votes

Answer: Option A


x=(3+i)/(2) or
x=(3-i)/(2)

Explanation:

Use the quadratic formula to find the zeros of the function.

For a function of the form


ax ^ 2 + bx + c = 0

The quadratic formula is:


x=(-b\±√(b^2-4ac))/(2a)

In this case the function is:


2x^2-6x+5=0

So


a=2\\b=-6\\c=5

Then using the quadratic formula we have that:


x=(-(-6)\±√((-6)^2-4(2)(5)))/(2(2))


x=(6\±√(36-40))/(4)


x=(6\±√(-4))/(4)

Remember that
√(-1)=i


x=(6\±√(4)*√(-1))/(4)


x=(6\±√(4)i)/(4)


x=(6\±2i)/(4)


x=(3\±i)/(2)


x=(3+i)/(2) or
x=(3-i)/(2)

User Mjwrazor
by
5.4k points